Partisipasi Masyarakat Terhadap Pembangunan Infrastruktur Jalan Di Kelurahan Panreng Kecamatan Baranti Kabupaten Sidenreng Rappang - Indah Mayasari; Sapri Sapri; AndiUceng Uceng (STISIPOL Raja Haji, 2025)
The main problem in this study is the still less than optimal community participation in road infrastructure development, which is seen from the damaged road conditions and the minimal involvement of residents in the planning process to the implementation of development. This study aims to determine community participation in road infrastructure development in Panreng Village, Baranti District, Sidenreng Rappang Regency. The population of this study was 1,501 family cards and a sample of 91 respondents determined using the Slovin formula and purposive sampling techniques. The type of research used is quantitative research. Data collection techniques were carried out through observation, questionnaires, and literature studies. Data analysis techniques were with the help of IMB SPSS statistics 26. The results of this study from the results of the questionnaire obtained a recapitulation of community participation variables of 65% in the